Sistem Informasi Manajemen dalam Data Pegawai Pendidikan - Faujiah, Hikmatul; zohriah, Anis; Muín, Abdul (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This study aims to find out how the benefits of management information systems in the knowledge of employee data. This research is library research. The results of the study conveyed that for knowledge, the data processing process functions as an executor of arithmetic, logical processes for data, storing and processing data programs, taking data input programs so that they can be used at any time, minimizing human labor, and getting more accurate results and minimal errors. The function of the database is to group data to facilitate data identification, the database prepares data in accordance with user requests for information quickly and accurately. Employee data has important value for organizations because it can be used to make informed decisions and improve operational efficiency. Good data can be organized in a database. The benefit of using a management information system is that it makes it easier for management to plan, direct, and supervise the course of business.